Forecasting Bull and Bear Markets: Evidence from China. Issue 8 (3rd August 2017) - Yu, Xiaojian; Chen, Zewei; Xu, Weidong; Fu, Junhui
ABSTRACT: This article extends previous empirical research to forecast Chinese bull and bear stock markets by using three types of binary probit time series models, which are static, autoregressive, and dynamic autoregressive models. This study shows that the dynamic auto regressive model performs the best both in- and out-of-sample. The inflation and market return variables significantly affect the market forecast. The dynamic autoregressive model has successfully forecast the bull and bear markets since 2007. The investment strategy based on this model performs better than the simple buy-and-hold strategy, especially after the Chinese government reformed the non-tradable shares in 2005.